The use of antifibrinolytics in pediatric patients with hypoproliferative thrombocytopenia. Issue 12 (24th May 2017) - Delaney, Meghan; Matthews, Dana C.; Gernsheimer, Terry B.
Abstract: Despite the use of evidence‐based platelet transfusion therapy during periods of hypoproliferative thrombocytopenia, a large proportion of pediatric hematology/oncology patients continue to suffer from clinically significant bleeding. Antifibrinolytic (AF) drugs have been shown in certain surgical and trauma settings to decrease bleeding, blood transfusion, and improve survival. We conducted a retrospective assessment of the safety of using AF drugs in pediatric patients with hypoproliferative thrombocytopenia at our center as well as the impact on bleeding occurrence and severity.